Functions Of Reporting Verbs In The Literature Review Of Master’s Theses In The Discipline Of Economics (ELT Worldwide: Journal of English Language Teaching, 2022)
Citation practices are realised through the use of reporting verbs which act as persuasive devices to achieve rhetorical impacts. Several studies have investigated citation practices in several disciplines in different contexts, with little done in the discipline of Economics. The study aimed to explore the citation practices in the literature review sections in master’s theses published in the Economics discipline. Using Hyland’s (2002) classification of reporting verbs, fifteen (15) literature review chapters were extracted from fifteen Economics master’s theses and analysed with AntConc software. Following the results of the study, it was revealed that all three types of reporting verbs were employed varyingly in the theses. Denotatively, the Discourse Acts was the frequently used category of the reporting verbs as compared to the Research Acts and Cognition Acts. On the evaluative function, findings and assurance verbs were employed frequently. While the study contributes to existing literature, it guides the practice of appropriate use of reporting verbs in academic writing.